A new ion exchange adsorption mechanism between carbonate groups and fluoride ions of basic aluminum carbonate nanospheres1. Issue 17 (27th February 2015) - Wei, Fang; Cao, Changyan; Huang, Peipei; Song, Weiguo
<x xml:space="preserve">Abstract</x> Basic aluminum carbonate nanospheres exhibited excellent adsorption properties for fluoride, and a new ion exchange mechanism involving carbonate groups and fluoride ions was proposed.